2003
DOI: 10.1086/378621
|View full text |Cite
|
Sign up to set email alerts
|

Bottoms Up! The Influence of Elongation on Pouring and Consumption Volume

Abstract: Although the effects of shapes on area perceptions have been widely investigated, we replicate, extend, and generalize one of the few studies to relate the effects of shapes to consumption volumes (Raghubir and Krishna 1999). While Raghubir and Krishna demonstrate the effect of the elongation of prepoured drinks on consumption volume, we have people pour their own drinks in a series of controlled field experiments. Two experiments in cafeterias show that both children and adults pour and consume more juice whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
193
2
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(209 citation statements)
references
References 18 publications
7
193
2
6
Order By: Relevance
“…Features such as the perceived variety of a food assortment (Kahn and Wansink 2004), and the size of plates, serving bowls, and/or utensils can all impact the quantity that will be consumed. For example, overweight teens consume less juice when pouring into a tall, thin glass relative to a short, wide glass, despite having estimated pouring more (Wansink and Van Ittersum 2003). Perceptual research can also be helpful in promoting a healthy diet.…”
Section: Creating a Healthy Home Environmentmentioning
confidence: 99%
“…Features such as the perceived variety of a food assortment (Kahn and Wansink 2004), and the size of plates, serving bowls, and/or utensils can all impact the quantity that will be consumed. For example, overweight teens consume less juice when pouring into a tall, thin glass relative to a short, wide glass, despite having estimated pouring more (Wansink and Van Ittersum 2003). Perceptual research can also be helpful in promoting a healthy diet.…”
Section: Creating a Healthy Home Environmentmentioning
confidence: 99%
“…Given this difficulty in interpreting percentages, consumers may be more susceptible to influences of a coloured area on pack. In another stream of research, consumer perceptions have been shown to depend on the spatial dimensionality of product packages (Chandon and Ordabayeva 2009;Wansink and van Ittersum 2003). That is, consumers perceive tall and narrow containers differently from short and wide containers, even when objectively their volume is the same.…”
Section: The Anchoring Effect In the Mars Casementioning
confidence: 99%
“…For example, in two studies, both adults and children underestimated the amount of liquid in short and wide glasses (24,25). In addition, people cannot accurately estimate the calories in various food items and underestimate calories depending on the context in which the foods are presented (26).…”
Section: Inability To Judge Volume or Calories Either Through Visual mentioning
confidence: 99%